Anaesthesia for endovascular aneurysm repair. Issue 5 (May 2019) - Barrett, John; Jones, Sian
Abstract: A patient with an abdominal aortic aneurysm can have surgical management through either an open or endovascular approach. The use of an endovascular approach has benefits for the patient by being a less invasive approach with initially lower mortality and morbidity and lower lengths of hospital stay, although longer term outcomes match open techniques. The endovascular technique requires more specialist equipment, including stents and imaging equipment. In the UK they are usually performed in specialist hospitals with teams of interventional radiologists, vascular surgeons and anaesthetists working together. Patients presenting for endovascular repair of their abdominal aortic aneurysm can present the anaesthetist with range of complex comorbidities which require specific management and optimization pre-operatively. The intraoperative management of the patient can vary, depending on patient, surgical and anaesthetic factors, from local anaesthetic, regional techniques or general anaesthesia. The postoperative complications are generally minimal, but the patients require lifelong follow up, making the procedure more expensive than an open procedure.